Antibacterial effect of endodontic sealers in root canals - Esmeralda Concha Camacho; Belen Chino; Aldo Cesar Acevedo Ortiz; Liliana Argueta-Figueroa (Editorial Ciencias Médicas, 2020)
Introduction: Endodontic sealers play a crucial role in sealing, for they not only act at the moment of their application, but continue to do so later, protecting the apical periodontium against microbial organisms. One of the properties desired in endodontic sealers is precisely their antimicrobial action against bacteria remaining after irrigation and instrumentation. Objective: Carry out a systematic review about the antibacterial effect of the endodontic sealers most commonly used in dental practice against Enterococcus faecalis (E. faecalis). Methods: The systematic review was based on PRISMA guidelines. The search was conducted in the databases PubMed and Science Direct. Papers were reviewed which dealt with in vitro antimicrobial studies about endodontic sealers, excluding secondary sources such as literature reviews and papers about cements used for other purposes. Discussion: Cements based on calcium hydroxide, resin or bioceramic are biocompatible and display some percentage of antimicrobial activity. However, variability was observed in the results obtained by the studies in the review, due to the use of different conditions for antibacterial evaluation, except for silicone-based endodontic sealers, which consistently displayed no antibacterial activity against E. faecalis. Conclusion: According to the bibliography reviewed, the sealers AH Plus, AH 26, TotalFill, BC Sealer and MTA Fillapex had an antimicrobial effect. However, some of them displayed scant activity against E. faecalis.